The Effect of CDKN1A on the Expression of Genes Related to Milk Protein and Milk Fat Synthesis in Bovine Mammary Epithelial Cells - Yuanyuan Zhang; Junxi Liang; Kai Zhang; Hong Su; Daqing Wang; Min Zhang; Feifei Zhao; Zhiwei Sun; Zhimin Wu; Guifang Cao; Yong Zhang (Veterinary Sciences, 2025)
Milk fat is an important nutritional component and flavor substance in dairy products. Its content and composition directly affect the nutritional value, processing characteristics, and economic benefits of dairy products. Therefore, an in-depth exploration of the molecular mechanisms that influence milk protein synthesis holds profound significance for dairy farming and dairy production. Molecular biology techniques were used to construct CDKN1A overexpression and interference vectors. Using BMECs (bovine mammary epithelial cells) as the experimental model, the vectors were transfected into the cells via liposome mediation to investigate the effect of CDKN1A on the expression of genes related to milk protein synthesis. The results showed that the CDKN1A overexpression and interference vectors were successfully constructed, and the overexpression of CDKN1A reduced milk protein synthesis, and the interference of CDKN1A enhanced milk protein synthesis. This finding provides an important theoretical basis for dairy farming and dairy production. By regulating the expression level of CDKN1A, it is possible to achieve precise control of milk protein yield in dairy cows. It also offers a potential target for the development of new feed additives or drugs. These additives or drugs can promote milk protein synthesis by regulating the activity of CDKN1A, providing new strategies and methods for the sustainable development of the dairy industry.